Organoleptic Evaluation of Manyung Fish Nugget Enriched with Moringa Leaves - Agustina, Sinta; Wahyudi, Anang; Suryani, Desri; Risda Yulianti (Jurnal Multidisiplin Madani, 2023)
This study examined the potential of using local ingredients such as Manyung fish (Arius thalassinus) and moringa leaves to create nutritious nuggets. The objectives of this study were to assess the organoleptic acceptability of Manyung fish nugget enriched with Moringa leaves concerning color, taste, aroma, and texture. The research followed an experimental approach using a randomized design. Findings indicated that the formulation F1 (90 g Manyung fish and 10 g moringa leaves), was favorable due to its superior attributes in color, taste, aroma, and texture. Among the formulations, F1 exhibited the most preferred in terms of sensory aspects. This research highlighted the potential of these local ingredients for nugget formulation especially for adolescent consumption